The Demand for Life Insurance in a Developing Country and The Mediating Role of Persuasion - Darian, Low Eng Swee; Robert, Jeyakumar Nathan; Eva, Gorgenyi-Hegyes; Maria, Fekete-Farkas (Centre of Sociological Research, 2021)
This study examines the demand for life insurance in a rapidly developing economic environment in South East Asia, focusing on Malaysia. The study extends the Elaboration Likelihood Model (ELM) by introducing a mediating variable ‘Persuasion’ in examining the demand for life insurance among policy buyers. Fuelled by the recent COVID-19 pandemic, the life insurance market is expected to grow significantly and the role of the state and regulatory body to regulate this process would be pivotal. Given the increasing significance of this industry both before and after the epidemic, this study identifies seven research variables from previous literature sources related to finance and international insurance, including financial literacy, saving motives, religiosity, risk aversion, agent, persuasion and purchase intention of life insurance. A causal research design is used to formulate research framework and testable hypotheses for this study. Data collection encompasses face to face interviews with 385 life insurance policy holders between May 2019 and March 2020 by using a survey questionnaire. Data analysis is mainly based on PLS-SEM method by using SPSS and Smart PLS statistical software packages. Results reveal persuasion as an important construct that explains the demand for life insurance, while agent is found to have the highest impact towards persuasion. The study also finds a full mediation effect of persuasion in the demand for life insurance for risk aversion and agent. These findings add new insights to the body of knowledge in life insurance literatures. Furthermore, research is useful for policy makers including government, finance, and insurance agencies; and recommends relevant strategies to further improve life insurance penetration in the population.